Implementation of the Problem-Based Learning Model in Islamic Education Subjects to Enhance Students' Problem-Solving Skills - Cahaya, Dosi; Ansori, Perik (PPSDP International Journal of Education, 2025)
The phenomenon of low problem-solving abilities among students at SMPN 8 Lebong, especially in the subject of Islamic Religious Education and Character Education, has become the main concern of this study. Students often struggle to relate religious concepts to everyday problems, resulting in underdeveloped critical thinking skills and problem-solving abilities. This study also aims to evaluate the impact of applying the Problem-Based Learning (PBL) model on enhancing students’ critical thinking and problem-solving skills. The method used in this research is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The data analysis technique used is interactive data analysis, which involves data reduction, data presentation, and drawing conclusions. Data validity is tested using triangulation, by comparing data from various sources to ensure the validity of the findings. The results of the study indicate that: 1) The planning of the PBL model successfully created learning scenarios relevant to students’ everyday lives, facilitating the development of their problem-solving skills. 2) The implementation of PBL was active with group discussions, case studies, and the application of deep problem-solving, enhancing collaboration among students. 3) Evaluation shows that the application of PBL improved students’ problem-solving abilities, with evidence of better problem analysis and more effective solutions. 4) This research shows that the application of the PBL model at SMPN 8 Lebong has a positive impact on improving students’ problem-solving abilities. The main supporting factors for the implementation of PBL include active student involvement, the role of an effective facilitator, and the application of relevant technology. However, there are also some inhibiting factors, such as limited resources, the lack of teacher training related to PBL, and time management challenges that affect the smoothness of the learning process.